Travellers in Faith or Stealthy Legions : The Gurage Role in the Rise of Tablighi Jama at in Ethiopia - Worku Hailemariam Mohammed (Oxford.: : Regnum Books International, 2023)
The Tablighi Jama at are an Islamic preaching movement in Ethiopia. This work explains the growth of Islam in Ethiopia in general and the Tablighi Jama at as an Islamic movement for faith renewal in particular. The majority view considers the movement as Travellers in Faith , a pietistic faith renewal, and peaceful movement with an apolitical position, whereas the minority views the Tablighi Jama at as Stealthy Legions , connected with terrorism and politics. The research shows that even though it is a transnational movement, Tablighi Jama at in Ethiopia manifests local identity and also maintains global connections, relevant to the current debate on faith and politics.
Keywords: Religion & Beliefs -- Islam; Islamic Theology